Structural Analysis of Bappeda’s Role in Stunting Convergence Actions in Maluku Province: Stunting in Maluku Province - Nendissa, Reghy Florencia; Purnomo , Daru; Hadiwijoyo, Suryo Sakti (Universitas Medan Area, 2024)
Stunting can also be caused by problems with nutritional intake consumed during pregnancy and toddlerhood. Lack of maternal knowledge about health and nutrition before pregnancy, as well as the postpartum period, limited health services such as antenatal services, and postnatal services low access to nutritious food, and low access to sanitation and clean water are also causes of stunting. These very diverse multi-factors require the most decisive intervention, namely at 1000 HPK (the first 1000 days of life). Factors Causing stunting are also influenced by the mother's work, father's height, mother's height, income, number of household members, parenting, and exclusive breastfeeding, besides stunting is also caused by several other factors such as maternal education, maternal knowledge about nutrition, exclusive breastfeeding, MP-ASI age, zinc, and iron adequacy levels, history of infectious diseases and genetic factors. Bappeda serves as the primary sector, capable of coordinating the entire element. The study aims to 1) describe the stunting dynamics in Maluku Province, 2) describe the implementation of stunting convergence in Maluku Province, and 3) structurally analyze the role of Bappeda in stunting conversion action in Maluku Province using Anthony Giddens' structure theory. This type of research is qualitative descriptive and interviews are used to gather data. The results of this study show that the prevalence rate of stunting in Maluku Province in 2022 reached 26.1%, which means that the rate of prevalence of stopping in 2022 has decreased amounted to 2.6% of SSGI's results in 2021 which reached 28.7%. Bappeda as a sector leader in the implementation of convergence plays a role as a planner and director, as well as as a coordinator and facilitator in facilitating the achievement of the goal of preventing increased stunting cases. Bappeda strives for synergistic collaboration across actors and sectors, especially in massive comprehensive education and advocacy in districts/cities to implement their respective work programs more effectively and efficiently.